The Effect of Floatable and Submerged Plants in Treating Drainage Waste Water in Egypt - Saffan, Samia Sayed; kamel, Gamal Abdel Naser; AL Shaboury, Abeer Mohammed (Journal of agricultural, environmental and veterinary sciences, 2017)
The study compares the effect of floatable and submerged plants on waste water treatment water samples were collected before and after the presence of the studied plants; floating and submerged one. Anatomical studied of some aquatic plant illustrated pollution parts. Germination experiments were carried out on some crops. El-khairy drain locate in El-Behaira governorate with length of 22.4 Km the study was considered in a reach of 8 Km. in water samples were collected seasonally and analyzed for Biological oxygen demand, Chemical oxygen demand, Nitrate, Cadmium, Lead, Cupper, Iron, ammonia, turbidity, total suspended solid and phosphate. All measured parameters were significantly decreased. compared the result of floating plants to that of submerged one illustrated that P-values of floating plants were more significant in Biological oxygen demand, Chemical oxygen demand, Nitrate, Cadmium, Lead, Cupper and Iron where submerged plants were more significant in removing ammonia, turbidity, total suspended solid and phosphate. The anatomical change illustrated heavy deposit of pollutant in plant cells. Germination experiment show significant increase in germination percent in corn, rice, sesame and wheat from low (60, 51.2, 37.5 and 68.33) detected on drain water to high (61, 77.5,45 and 80) in water after pass on aquatic plans.
Keywords: Floating; submerge; anatomical; germination percent; drainage water